ASYMMETRIC IMPACT OF SINGAPORE AND MALAYSIA’S STOCK MARKET VOLATILITY SPILLOVER ON INDONESIA - Mbui, Martinius Christian (Penerbit Atma Jaya Catholic University of Indonesia, 2019)
This paper studies the impact of the integration of all capital markets throughout the ASEAN Economic Community countries with Indonesia?s stock market. The integration will cause information being transmitted without border to all stock markets within the ASEAN Countries. This condition can lead to the increase of spillover volatility effect and moreover asymmetric spillover volatility phenomenon. Singapore and Malaysia are the most influential countries in ASEAN. Singapore is an advanced country within the ASEAN region and has played an important role. Malaysia is another developing country in ASEAN with a better stock market compared to other ASEAN countries. Malaysia also has great GDP and economic growth. Thus, it is possible that the shock in Singaporean and Malaysian stock market will be transmitted to all countries within the ASEAN region, especially Indonesia. Using T-GARCH (1,1), we were able to capture the spillover volatility effect from Singapore and Malaysia toward the Indonesian Stock Exchange, although only Singapore has the asymmetry effect on the Indonesian Stock Market. Therefore, the negative return at the Singapore stock exchange will be transmitted to Indonesia with a bigger impact compared to a positive return.